Control premium minority discounts in Polish business valuation practices: Evidence from research - Katarzyna Byrka-Kita; Michał Grudziński (e-Finanse: Financial Internet Quarterly, 2017)
The paper presents the results of a survey of business valuation practice in Poland. The aim of this study was to assess the premium for control as well as discounts for minority interests by practitioners involved in the valuation of companies in Poland. The survey was conducted on a sample of 191 respondents between February and April 2011. The population of entities under survey consists of: authorized NewConnect3 / Catalyst advisers, brokers, valuation analysts working for leading consulting firms, and experts appointed by the court. The evidence from the research demonstrates that most of respondents do not know how to apply premium control and minority discounts in business valuation. Incorrect approaches to the application of control premiums or minority discounts reflect that this area of valuation lacks thorough analysis in the Polish market. As a consequence, particularly in the case of lawsuits it may cause unjustified transfers of value between the parties.
Keywords: G32; G34; G12; 330; business valuation; control premium; minority discounts; ownership structure; valuation practice